Comparative efficacy and acceptability of pharmacotherapies for postpartum depression: A systematic review and network meta-analysis - Zhang, Qing; Dai, Xiaoli; Li, Wei (Frontiers in Pharmacology, 2022)
Purpose: To evaluate the efficacy and tolerability of pharmacotherapies for postpartum depression (PPD). Method: We performed a computerized search of MEDLINE (Ovid and PubMed), Embase, Cochrane Library, Web of Science, and Google Scholar to identify eligible randomized controlled trials (RCTs) before 31 March 2022. We calculated standardized mean differences (SMDs) for continuous outcomes and odds ratios (ORs) for dichotomous outcomes with the random-effects model. The tolerability of antidepressants in terms of early dropouts was investigated. The surface under the cumulative ranking curve (SUCRA) was used for ranking the outcomes. Quality assessment of the included studies was performed using the Cochrane Collaboration’s tool. Results: A total of 11 studies with 944 participants were included in this network meta-analysis, involving nine antidepressants. With respect to efficacy, only estradiol and brexanolone were significantly more effective than the placebo (p < 0.05), and the calculated SUCRA indicated that estradiol (94.3%) had the highest probability ranking first for reducing the PPD, followed by paroxetine (64.3%) and zuranolone (58.8%). Regarding tolerability, a greater percentage of patients treated with brexanolone experienced early dropout as compared to those treated with most other antidepressants. Conclusion: Only estradiol and brexanolone showed significantly higher efficacy than the placebo. According to the SUCRA ranking, estradiol, paroxetine, and zuranolone were the three best antidepressants. Concerning acceptability in terms of early dropouts, brexanolone was less well-tolerated than other antidepressants.